Sensemaking and sensegiving in strategic change initiation - Gioia, Dennis A.; Chittipeddi, Kumar (Strategic Management Journal, 1991)
Abstract This paper reports an ethnographic study of the initiation of a strategic change effort in a large, public university. It develops a new framework for understanding the distinctive character of the beginning stages of strategic change by tracking the first year of the change through four phases (labeled as envisioning, signaling, re‐visioning, and energizing). This interpretive approach suggests that the CEO's primary role in instigating the strategic change process might best be understood in terms of the emergent concepts of ‘sensemaking’ and ‘sensegiving’. Relationships between these central concepts and other important theoretical domains are then drawn and implications for understanding strategic change initiation are discussed.